The pattern of use of toothpaste among family members in Tehran Iran - Sorour Soltani; Hossein Hessari; Reza Yazdani (Babol University of Medical Sciences, 2020)
Introduction: Oral health can influence general health and then the quality of life. Regular toothbrushing with toothpaste plays a fundamental role in oral hygiene. The aim of this study was to assess the pattern of utilization of toothpaste among Iranian population. Materials & Methods: This cross-sectional study evaluated the family members of patients (n=715) presenting to dental clinics of School of Dentistry of Tehran University of Medical Sciences, in 2017. A researcher-made questionnaire was used to collect information regarding the pattern of utilization of toothpaste by the subjects. Data were analyzed using Chi-square test via SPSS 25. Results: Of all, 81% participants reported that they personally use toothpaste when toothbrushing and 75.9% stated that all the family members used toothpaste when brushing their teeth. Moreover, 57.2% reported that all the family members shared the same toothpaste; 86.6% reported that they started brushing the teeth of their children at the age of 3 years. When asked about the factors considered when for purchasing - toothpaste, the most important factors were the manufacturing country (42.5%), date of production (38.7%), having standard and authenticity labels (29.5%), the price (29.5%). Conclusion: According to the results, Iranian families have inadequate knowledge about the correct pattern of use of toothpastes.